Strengthening and toughening of Cu matrix composites reinforced by metallic glass particles with variable size. (March 2023) - Bao, Weizong; Yang, Xinxin; Chen, Jie; Xiang, Tao; Zhou, Toujun; Xie, Guoqiang
Highlights: The strength and plasticity of the composites increase simultaneously with the reduction in size of the metallic glass reinforcement. The strength of the composite is mainly provided by grain boundaries and metallic glass reinforcements, with fine and dispersed reinforcements contributing more to the strength. Crack extension behavior under uniaxial compression is observed for composite sections. Abstract: Metallic glass particle reinforced CuCrZr composites with excellent mechanical and electrical properties are manufactured by ball milling and spark plasma sintering. The effect of reinforcement size on the microstructure and properties of composites is investigated. As the size of metallic glass particles decreases, the strength and toughness of the composites are jointly increased. Quantitative results of the strengthening mechanism show that the strength is mainly provided by grain boundaries and metallic glass particles, with the fine and dispersed metallic glass reinforcements contributing more to the strength. Furthermore, crack extension behavior under uniaxial compression is observed for composite sections. The results indicate that cracks sprout and expand along the interface, and the interface bonding modified by the ball milling (BM) process can effectively inhibit the crack merging process. In particular, the crack extension rate corresponds to the plasticity of the particle-reinforced composite as determined by the interfacial properties, particle size and distribution of the reinforcement.